2015
DOI: 10.1155/2015/671632
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wind-Induced Vibration of Transmission Tower-Line System by Using a Spring Pendulum

Abstract: The high-voltage power transmission tower-line system, which is a high flexible structure, is very susceptible to the wind-induced vibrations. This paper proposes the utilization of the internal resonance feature of the spring pendulum to reduce the wind-induced vibration of a transmission tower. The kinetic expression of the spring pendulum system is obtained through Lagrangian equation. The condition of the internal resonance is verified to be = 2, in which is the ratio of the spring mode frequency over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…To simplify the numerical calculation, the transmission tower is simplified to 23 nodes, where the node number increases from the top to bottom. The damping matrix is obtained by the Rayleigh damping formula and the damping ratio is usually set to 0.02 . The first‐order natural frequency of the simplified transmission tower is 0.96 Hz.…”
Section: Numerical Analysis Of a Transmission Tower Controlled By An Smpmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the numerical calculation, the transmission tower is simplified to 23 nodes, where the node number increases from the top to bottom. The damping matrix is obtained by the Rayleigh damping formula and the damping ratio is usually set to 0.02 . The first‐order natural frequency of the simplified transmission tower is 0.96 Hz.…”
Section: Numerical Analysis Of a Transmission Tower Controlled By An Smpmentioning
confidence: 99%
“…Chen et al used magnetorheological dampers to control the wind‐induced response of a transmission tower‐line system and proposed two semi‐active control strategies for the vibration mitigation of tower‐line systems. Zhang et al proposed a spring pendulum to reduce the vibration of a transmission tower. Their results showed that the spring pendulum is extremely effective in reducing seismic‐induced vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible thread is a peculiar spring that works only for stretching. In a typical two-dimensional model, flexible thread can simultaneously perform transverse oscillations in its plane (analogous to angular oscillations of the loaded swinging spring) and pendulum oscillations which connect support attachments (analogous to vertical oscillations) [6], for example, wires of high-voltage lines whose state is influenced by wind gusts. Loss of dynamic stability occurs at a ratio of 1:2 of frequencies of the indicated oscillations and then transverse oscillations of the thread appear with amplitude reaching rather large values.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting GFRP cross arm in transmission tower can improve the reliability of power supply through reducing the negative effects of partial discharge and contamination flashover, while it can obtain the significant economic benefits by reducing the width of the transmission line corridor and maintenance costs. However, the fatigue load of GFRP cross arms caused by wind-induced vibrations is a safety problem that cannot be neglected in the design period [3,4]. Actually, fatigue failure is one of the most important failure types of GFRPs during their service.…”
Section: Introductionmentioning
confidence: 99%